Respiratory heat loss of Holstein cows in a tropical environment - Maia, ASC; DaSilva, R. G.; Loureiro, CMB (Springer, 2005)
In order to develop statistical models to predict respiratory heat loss in dairy cattle using simple physiological and environmental measurements, 15 Holstein cows were observed under field conditions in a tropical environment, in which the air temperature reached up to 40 &DEG; C. The measurements of latent and sensible heat loss from the respiratory tract of the animals were made by using a respiratory mask. The results showed that under air temperatures between 10 and 35 &DEG; C sensible heat loss by convection decreased from 8.24 to 1.09 W m(-2), while the latent heat loss by evaporation increased from 1.03 to 56.51 W m(-2). The evaporation increased together with the air temperature in almost a linear fashion until 20 &DEG; C, but it became increasingly high as the air temperature rose above 25 &DEG; C. Convection was a mechanism of minor importance for respiratory heat transfer. In contrast, respiratory evaporation was an effective means of thermoregulation for Holsteins in a hot environment. Mathematical models were developed to predict both the sensible and latent heat loss from the respiratory tract in Holstein cows under field conditions, based on measurements of the ambient temperature, and other models were developed to predict respiration rate, tidal volume, mass flow rate and expired air temperature as functions of the ambient temperature and other variables.
Keywords: thermoregulation; cows; respiration; tropical environment; heat loss